2022
DOI: 10.1186/s13643-022-01998-1
|View full text |Cite
|
Sign up to set email alerts
|

The Campbell Collaboration’s systematic review of school-based anti-bullying interventions does not meet mandatory methodological standards

Abstract: Background Many published reviews do not meet the widely accepted PRISMA standards for systematic reviews and meta-analysis. Campbell Collaboration and Cochrane reviews are expected to meet even more rigorous standards, but their adherence to these standards is uneven. For example, a newly updated Campbell systematic review of school-based anti-bullying interventions does not appear to meet many of the Campbell Collaboration’s mandatory methodological standards. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 63 publications
0
1
0
1
Order By: Relevance
“…Sittemmin edellä mainitun meta-analyysin tekijät ovat tehneet uuden metaanalyysin kiusaamisinterventioiden tehokkuudesta (Gaffney ym., 2021). Sen tilastollinen luotettavuus on tullut kyseenalaistetuksi muun muassa siksi, että kriteerit sille, miten aineisto on valittu mukaan, eivät ole läpinäkyvät, ja sen vuoksi tutkimuksessa mukana olevien kiusaamisen vastaisten interventioiden toimivuudesta voi tulla liian positiivinen tulos ja analyysin luotettavuus voi vaikuttaa suuremmalta kuin se on (Littell & Gorman, 2022). Ajankohtaisessa tutkimuksessa on myös nostettu esiin kysymys siitä, kuinka hyvin ylipäätään kvantitatiivisen tutkimuksen avulla voidaan tutkia monimutkaisia sosiaalisia prosesseja tai esimerkiksi lasten ja nuorten omia näkemyksiä kiusaamisesta (esim.…”
Section: Yksilöllistävän Kiusaamistutkimuksen Haasteetunclassified
“…Sittemmin edellä mainitun meta-analyysin tekijät ovat tehneet uuden metaanalyysin kiusaamisinterventioiden tehokkuudesta (Gaffney ym., 2021). Sen tilastollinen luotettavuus on tullut kyseenalaistetuksi muun muassa siksi, että kriteerit sille, miten aineisto on valittu mukaan, eivät ole läpinäkyvät, ja sen vuoksi tutkimuksessa mukana olevien kiusaamisen vastaisten interventioiden toimivuudesta voi tulla liian positiivinen tulos ja analyysin luotettavuus voi vaikuttaa suuremmalta kuin se on (Littell & Gorman, 2022). Ajankohtaisessa tutkimuksessa on myös nostettu esiin kysymys siitä, kuinka hyvin ylipäätään kvantitatiivisen tutkimuksen avulla voidaan tutkia monimutkaisia sosiaalisia prosesseja tai esimerkiksi lasten ja nuorten omia näkemyksiä kiusaamisesta (esim.…”
Section: Yksilöllistävän Kiusaamistutkimuksen Haasteetunclassified
“…ORB ratings appear to be perfunctory in some reviews, indicating that there is room for improvement in methods of assessing ORB. For example, a prominent Campbell review (Gaffney et al, 2021) assessed ORB as "low risk" in most included studies but provided no support for these ratings; independent attempts to replicate these ratings (using the review's stated criteria) with 41 studies showed very low (7%) agreement (κ = 0.003; Littell & Gorman, 2022).…”
Section: Partialmentioning
confidence: 99%